Evaluation of students learning outcomes on engineering surveying - Boon Hoe, Goh; Choon Lai, Chiang; Lee Guat Poh, Betsy; Muthoosamy, Kasturi (International Journal of Engineering and Technology, 2019)
Outcomes Based-Education (OBE) is a learning approach that cultivates student centered learning and emphasises on students’ attributes, and it is becoming the mutual agreement by the signatory countries of Washington Accord 1989 to embed the OBE into their engineering education system. The implementation of OBE in an accredited engineering degree involves the design of OBE curriculum by setting the Programme Education Objectives (PEOs), Programme Outcomes (POs) and Module Learning Outcomes (MLOs), and measurement of the attainment of POs and MLOs. This paper presents the evaluation and attainment of POs on Engineering Surveying via Survey Field Course, based on students’ self-evaluation approach, before-and-after attending the course. Five programme outcomes as required by Board of Engineers Malaysia were evaluated and the study revealed that only two programme outcomes (communication, and individual and team work) were not attained and need attention for future improvements.